Lived experiences of Malaysian family caregivers of patients with chronic illnesses: A qualitative study - Nurul Salwa Sajali; Norfaezah Md Khalid; Norsafatul Aznin A Razak (Malaysian Family Physician)
Introduction: Chronic illnesses have added to the demand in informal caregiving. Culturally, family members are expected to provide physical care and psychosocial support to their sick members, but the challenges they face have adversely impacted their employment, financial, physical and emotional wellbeing. This study aimed to explore the lived experiences of family caregivers of patients with chronic illnesses. Methods: This qualitative research was based on the interpretative phenomenological analysis (IPA) approach. Purposive sampling was used to recruit five family caregivers of patients with chronic illnesses. Data were collected through in-depth semi-structured individual interviews and document analysis and later analysed systematically according to the six-step IPA process. Results: The data revealed the informants’ meaning of experience in four themes: 1) adversities, 2) adjustment challenges, 3) adaptation and acceptance and 4) identity. Conclusion: The findings suggest that constructive lived experiences may be cultivated by increasing knowledge in caregiving, receiving greater appreciation and support from family members and learning to embrace the new identity. Caregiver support programmes or workshops focusing on emotional resilience or communication strategies can help to boost the positive life experiences of caregivers. The findings can be useful for healthcare professionals in understanding and addressing the needs of caregivers and improving the support and services provided to them.